2020
DOI: 10.3844/crdsp.2020.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Sialoliths: A Radiographic Retrospective Study

Abstract: Sialoliths are salivary gland calcifications that mainly affect submandibular and parotid glands. They are detected incidentally on dental panoramic radiographs. This study aimed to determine the prevalence of sialoliths in a Lebanese sample and evaluate the site, gender and age distribution of such findings. In this retrospective study, 500 digital panoramic radiographs, belonging to 219 males and 281 females aged 18-88 years, were examined to identify sialoliths seen as radiopacities in the parotid, submandi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…13 An important radiographic retrospective study performed by Aoun et al, which included 500 OPG images of patients with different pathology, showed that submandibular sialoliths were noted only in 1.8% of cases and parotid sialoliths only in 1.2% of cases. 21 Cases presented in this essay clearly showed the radiologic features of sialoliths located in the submandibular gland and Wharton's duct. Sialoliths in our cases are visualized as single or multiple radiopaque lesions being a completely different form -elongated, round, and teardrop-shaped.…”
Section: Discussionmentioning
confidence: 76%
“…13 An important radiographic retrospective study performed by Aoun et al, which included 500 OPG images of patients with different pathology, showed that submandibular sialoliths were noted only in 1.8% of cases and parotid sialoliths only in 1.2% of cases. 21 Cases presented in this essay clearly showed the radiologic features of sialoliths located in the submandibular gland and Wharton's duct. Sialoliths in our cases are visualized as single or multiple radiopaque lesions being a completely different form -elongated, round, and teardrop-shaped.…”
Section: Discussionmentioning
confidence: 76%
“…13 An important radiographic retrospective study performed by Aoun et al, which included 500 OPG images of patients with different pathology, showed that submandibular sialoliths were noted only in 1.8% of cases and parotid sialoliths only in 1.2% of cases. 21 Cases presented in this essay clearly showed the radiologic features of sialoliths located in the submandibular gland and Wharton's duct. Sialoliths in our cases are visualized as single or multiple radiopaque lesions being a completely different form -elongated, round, and teardrop-shaped.…”
Section: Discussionmentioning
confidence: 76%